KINETIKA REAKSI FERMENTASI ALKOHOL DARI BUAH SALAK - Fatimah, Febrina Lia G, Lina Rahmasari G (Jurnal Teknik Kimia USU, 2013)
Research about bioethanol production from salak that are not marketable has been done. Salak containing 16.07% starch and 32.96% glucose, so that salak is potential to be converted into bioethanol by fermentation. This research aimed to study reaction kinetic of alcoholic fermentation that are the reaction kinetic of the hydrolysis of starch to glucose and fermentation of glucose to alcohol from salak by using Saccharomyces cereviseae. Hydrolysis of starch reaction containing two reaction rate controls that are chemical reaction and film diffusion. The results obtained for the hydrolysis reaction that the reacion rate constant is 1,41 x 10-11 and the film diffusion coefficient constant is 0,47 x 10-11 so the rate of the hydrolysis reaction is controlled by the film diffusion. Reaction rate constant for fermentation is 169,88. During the process of fermentation, the concentration of starch and glucose tended to decreased by time of fermentation and bioethanol concentration tended to increase by time of fermentation. Keywords : fermentation, hydrolysis, bioethanol, reaction kinetics